Management Strategy Of Village-Owned Enterprises (Bumdes) In Moncongloe Village, Lappara, Moncongloe District, Maros Regency - Aras Solong; Muhammad Nadhar; Sarnia Sarnia (Cita Konsultindo Research Center, 2023)
Management Strategy Badan Usaha Milik Desa (BUMDes) in Moncongloe Lappara Moncongloe Maros written by Aras Solong and Sarnia. This study aims to determine the management strategy of village-owned enterprises (BUMDes) and the factors that influence the management strategyof village-owned enterprises (BUMDes) in Moncongloe Village, Lappara, Moncongloe District, Maros Regency. The type of research used is qualitative research with data collection techniques through observation, interviews and documentation with data analysis using word reduction, data presentation, and conclusions. The results showed that there are three management strategies applied to village-owned enterprises (BUMDes), namely: (a) Strategy formulation refers to determining programs or references in the implementation of vision and mission, as well as setting long-term and short-term goals. (b) Strategy execution, refers to decisions made to strengthen existing strategies. (c) The stages of strategy evaluation refer to the vision and mission and programs that have been determined to run well or vice versa, while the factors that can affect the management strategy there are two factors that affect the management strategy, namely budget factors and human resource (HR) factors . From the research, it was found that the management strategy has worked well and influencing factors can be found solutions so that the management of BUMDes runs well